Tinjauan Hukum Administrasi Negara Atas Penerapan Sertifikat Tanah Elektronik oleh PPAT dan Notaris Gunungkidul, DIY - Putri, Audria Darel Setiawan; Nugroho, Asianto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the role of PPAT and Notaries in the digital transformation of land certificates in Gunungkidul Regency, triggered by the issuance of Minister of ATR/Ka BPN Regulation No. 1 of 2021 on Electronic Certificates. The regulation's implementation is phased and has not been uniformly applied across Indonesia, including in Gunungkidul Regency. The study aims to explore the urgency of PPAT and Notaries' roles, obstacles encountered in the digital transformation process, and its implications from a State Administrative Law perspective. Using a combination of normative and empirical legal methods, the research employed qualitative descriptive analysis and normative analysis techniques. Data collection was conducted at the Wonosari District PPAT Office, the INI Wonosari Office, and the ATR/BPN Gunungkidul Regency Office. The findings highlight that PPAT and Notaries play essential roles in electronic certificate verification, electronic processing, creation of land zoning files, and land registration. Electronic certificates enhance data security, validity, and prevent duplication or forgery. However, obstacles such as limited human resource competence, inadequate office infrastructure, unintegrated data, and the need for document formalization hinder optimal implementation. External challenges include public unfamiliarity with digital technology and device ownership limitations. From the perspective of State Administrative Law, PPAT and Notarial deeds are formalized under civil law, not public law, and are not classified as unilateral acts (beschikking). This is confirmed by court decisions, including Decision No. 22/PUT.TUN/1993/PTUN.SBY and Decision No. 34 PK/TUN/2001, which clarify that such deeds cannot be disputed in State Administrative Court